Flu bug provides unhealthy lesson - Abd Razak, Dzulkifli (2009)
Mexico hosted two important international conferences on higher education last week in Guadalajara. A historic city, Guadalajara is named after another city in Spain and the name is said to originate from the Arabic WadialHajara meaning "Valley of Stones". Malaysia has an Honorary Consul in this nice and beautiful city. We can certainly learn a lot from this historic city, known as Mexico's silicon valley, which has rich cultural diversity.